Professor: profissão de risco: a percepção das condições de trabalho por docentes em IES privadas no Rio de Janeiro - Ferreira, Paula Cristina Afonso dos Santos (2012)
The present study has as its object the teaching work in Private Higher Education Institutions in Rio de Janeiro. The effort throughout the research was to analyze the relations and conditions of teaching in private higher education institutions, and for this we selected three institutions in Rio de Janeiro. A characterization of higher education institutions surveyed from some variables highlighted by the author. For it was possible to analyze the data was necessary to go through the existing literature on the subject. Through the analysis of the theoretical issues concerning the teaching in the country, the semi-structured interviews and participant observation were investigated issues such as arrangements for teaching, qualification teaching, management practices in higher education institutions private contemporary legislation and others. It was found that factors such as excessive number of students in the classroom, high number of classes to maintain the livelihood and job insecurity are factors that t igger instability in teaching. The institution where they perform their work activities do not bring security for the future.